Case Study : Nordin Batik & Craft Sdn Bhd / Mimi Nor Shazleen Hanafiah - Hanafiah, Mimi Nor Shazleen (2021)
Batik was known in the Malay world through stories of trade going on here. Some researchers have made a study of the relationship in the Malay batik. The influence of the Malay in the Malay Peninsula as well as developments in the Malay batik many starting to trade the past by merchants who came to trade to Malaya. The batik industry is one of the Small and Medium Industries which is the backbone of the country's industrial sector. Batik is believed to be derived from the Javanese words ‘ba’ and ‘tik’ which mean a drop of wax. In the book "Arts and Craft In Indonesia" the word batik comes from 'ambatik' which is a fabric made of small and fine dots also means 'tik' meaning the Javanese word, 'tritik' or 'taritik'. According to Tan Sri Makmun Murod, “some people think that the existence of the word ‘ti-tik ’is due to the process and the word is blocked because it follows the pattern of the process which produces small dots on the fabric. This definition does not include screen batik that does not go through the above process but it is still called batik. Batik is a handicraft art that relies heavily on handicrafts (manual) through its processes performed by humans alone and assisted by relatively traditional tools. Batik is processed using four specific techniques namely Block, Block and stencil, Block and Canting, and Canting or scratch. In general, Kelantan is a state that is known as a state rich in various fine and high-quality works of art. Among them are songket, silver carpentry, moon kite and handicrafts including batik. Batik is a fine and interesting art because it demands high expertise and finesse. Among the well-known and well-known batik entrepreneurs in Kelantan are Tuan Haji Nordin Bin Mahmood. He was one of the earliest people to pioneer the batik industry in Kelantan and a batik figure who still stands strong in the batik arena until now. As a result of tireless hard work and high commitment, he never tired of venturing into the batik sector and has been through hardships throughout his involvement of more than forty -nine years in this field. Now, he is able to be proud of his hard work over the years with the magnificent construction of Wisma Nordin, which is the first and largest batik exhibition and sales center in the state of Kelantan that was once owned by the bumiputeras, especially among Kelantan batik entrepreneurs.